Green building and design - Campbell, Andrea (Princeton, NJ : Films for the Humanities & Sciences, 2007)
The history of Western architecture can be viewed as a battle--namely, humanity vs. nature. But the green revolution has prompted new forms of building design that welcome in the natural world. This program surveys some of those advances and the architectural pioneers who create and implement them.
Originally released c2005. Originally produced as an episode of the television series Ethical markets in 2005.
Co-executive producers, Hazel Henderson, Ellyne Lonergan.
Host, Simran Sethi.
DVD format.
Keywords: Sustainable buildings -- Design and construction; Sustainable architecture; Sustainable development